(untitled) (Research, Society and Development, 2021)
Objectives: To investigate the perception of professionals who work in a public hospital, in relation to orthothanasia and palliative care in the elderly, also considering the profile of health professionals working in the place, if the type of professional training affects the team’s choices to the end of life and the need to update professionals on orthothanasia. Methods: This was a cross-sectional study, with a qualitative and quantitative approach, in a public hospital in Campina Grande-PB, with the application of an interview to a multidisciplinary team. Results: It was noticed that orthothanasia is known by professionals, although few feel able to perform it. There was little knowledge of these to institute palliative care, a phenomenon that did not show a significant association with the type of training (Chi-square = 0.98, p = 0.32) or the type of institution where the training was completed (Chi-square = 1.63, p = 0.20), but presented a moderate (Cramer V = 0.48, p = 0.002) and significant (Chi-square = 9.40, p = 0.002) relationship with the fact that the professional has or not some specialization. Regarding the difficulties faced in caring for terminally ill patients, dealing with their families was considered the main one. As for the tools necessary to make orthothanasia feasible in the elderly, improving knowledge and approach on the topic had a higher prevalence. Conclusion: It was concluded that there is a need to expand the theme in the training of professionals, in order to enable truly humanized assistance to the elderly.